Distinct inflammatory mediator patterns in young black and white adults: The African-predict study. (February 2020) - Crouch, Simone H.; Roux, Shani Botha-Le; Delles, Christian; Graham, Lesley A.; Schutte, Aletta E.
Highlights: Black and white groups present with unique inflammatory mediator patterns. Patterns are independent of blood pressure, sex or social class. No association with blood pressure was seen in either black or white groups. Young 20–30 year, healthy, adult study population. Abstract: Objective: Inflammatory mediators have been implicated in the early stages of cardiovascular disease development, including hypertension. Since global reports reflect a higher hypertension prevalence in black than white populations, we hypothesise the involvement of specific inflammatory mediators. We therefore compared a detailed range of 22 inflammatory mediators between young black and white adults, and determined the relationship with blood pressure. Approach and results: We included 1197 adults (20–30 years; 50% black; 52% female) with detailed ambulatory blood pressures. Blood samples were analysed for 22 inflammatory mediators. For pro-inflammatory mediators, the black adults had higher C-reactive protein, interferon-inducible T-cell alpha chemoattractant, macrophage inflammatory protein 3 alpha (all p ≤ 0.008), but lower interferon-gamma, interleukin (IL)-1β, IL-8, IL-12, IL-17A, and tumour necrosis factor alpha (all p ≤ 0.048). For anti-inflammatory mediators the black group consistently had lower levels (IL-5, IL-10 and IL-13 (all p ≤ 0.012)), resulting in generally higher pro-to-anti-inflammatory ratios in black than white adults (p ≤ 0.001). In mediators with pro- and anti-inflammatory functions, the black group had lower granulocyte-macrophage colony-stimulating factor and IL-6 (both p ≤ 0.010). These patterns were confirmed after adjustment for age, sex and waist circumference, or when stratifying by hypertensive status, sex and socio-economic status. Multi-variable adjusted regression analyses and factor analysis yielded no relationship between inflammatory mediators and blood pressure in this young healthy population. Conclusions: Black and white ethnic groups each consistently presented with unique inflammatory mediator patterns regardless of blood pressure, sex or social class. No association with blood pressure was seen in either of the groups.